Do patients with obstructive sleep apnea have thick necks? - Katz, I; Stradling, J; Slutsky, A; Zamel, N; Hoffstein, V (1990)
During physical examination of patients with suspected obstructive sleep apnea (OSA), a comment is frequently made that they appear to have a short and fat neck. To confirm this subjective impression by objective measurements, we studied a group of 123 patients referred to us because of snoring and suspected OSA, all of whom had nocturnal polysomnography and measurements of external and internal neck circumference. The external neck circumference was measured at the level of the superior border of the cricothyroid cartilage. Internal neck circumferences were calculated from the measurements of pharyngeal, glottic, and tracheal areas obtained by the acoustic reflection technique. Internal pharyngeal circumference was further subdivided into the proximal, middle, and distal thirds. The acoustic technique also permitted us to measure the distance between the teeth and the glottic minimum, which reflects the length of the upper airway. Stepwise multiple linear regression analysis revealed that the apnea/hypopnea index (AHI) correlated only with the external neck circumference, the body mass index, and the internal circumference of the distal pharynx; these three variables accounted for 39% of the variability in AHI. We conclude that the external and internal neck circumferences and the degree of obesity are important predictors of sleep apnea; it is possible that obesity produces its effect via fat in the neck. We speculate that the static pharyngeal size modulated by the dynamic loading of the airway due to the weight of fatty tissue of the neck may contribute to the pathogenesis of OSA.